2016
DOI: 10.1111/wrr.12466
|View full text |Cite
|
Sign up to set email alerts
|

Clinical interventions for venous leg ulcers: Proposals to improve the quality of clinical leg ulcer research

Abstract: The present status of clinical leg ulcer healing research was reviewed by 25 experts over 2 days on September 28 and 29, 2015. Multiple clinical effectiveness reviews were presented suggesting that published clinical wound healing research often does not meet present (2015) evidence based standards. Specific areas requiring remediation were highlighted and approaches to overcoming existing challenges were proposed. Participants using anonymous voting technology developed an action plan to resolve perceived def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Larger trials are needed in wound care. Lazarus et al found that among 63 prospective VLU trials, the median number of participants was a trifling 37 . Recent RCTs from our research network show higher enrollment numbers, with more than 80 patients enrolled, but these enrollment numbers make up less than 10% of the number of patients with VLUs in the consortium (Table ).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Larger trials are needed in wound care. Lazarus et al found that among 63 prospective VLU trials, the median number of participants was a trifling 37 . Recent RCTs from our research network show higher enrollment numbers, with more than 80 patients enrolled, but these enrollment numbers make up less than 10% of the number of patients with VLUs in the consortium (Table ).…”
Section: Discussionmentioning
confidence: 87%
“…The impetus on the part of the FDA to utilize RWD is an opportunity for the wound care community to overcome the barriers that have, until now, prevented the creation of a LHS focused on wound care. We have been caught in a vicious cycle wherein RCTs exclude real‐world patients, with the result being that the evidence base derived from these studies that does not apply to real‐world patients . Consequently, clinicians, patients, and payers are hindered in their decision making, because limited evidence is available to determine the best treatment for a chronic wound .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations